Ongoing problems concerning 7th TNM Staging System and Proposals for 8th TNM Staging System of Gastric Cancer - Ilhan, Enver; Ureyen, Orhan; Meral, Ulvi Mehmet (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Because of different prognosis of gastric cancer patients with the same T and N stages, the impossibility of N3 staging in patients with fewer than 15 removed lymph nodes, and the presence of stage migration phenomenon, the 6th edition TNM Staging System for gastric cancer was updated to the 7th edition TNM staging system in 2009. Despite some opposing views, the superiority of the 7th edition TNM staging system compared to the 6th has been demonstrated in many studies. However, there are doubts about the 7th edition that it will reduce the stage migration phenomenon. The most important problem about the 7th TNM staging system is regarding subgroups N3a and N3b. The separation of N3 stage as N3a and N3b does not contribute to the TNM staging system. In conclusion, separate usage of N3a and N3b subgroups in the TNM staging system should be considered in the creation phase of the 8th edition.